Boosting yields in drought-prone areas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A drought-tolerant variety of sorghum, S-35, developed by breeders at the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) and partner institutes, is being widely adopted in Cameroon and Chad.